Aryl hydrocarbon receptor (AHR) is a potential tumour suppressor in pituitary adenomas. Issue 8 (August 2017) - Formosa, R; Borg, J; Vassallo, J
Abstract : Pituitary adenomas (PA) represent the largest group of intracranial neoplasms and yet the molecular mechanisms driving this disease remain largely unknown. The aim of this study was to use a high-throughput screening method to identify molecular pathways that may be playing a significant and consistent role in PA. RNA profiling using microarrays on eight local PAs identified the aryl hydrocarbon receptor (AHR) signalling pathway as a key canonical pathway downregulated in all PA types. This was confirmed by real-time PCR in 31 tumours. The AHR has been shown to regulate cell cycle progression in various cell types; however, its role in pituitary tissue has never been investigated. In order to validate the role of AHR in PA behaviour, further functional studies were undertaken. Over-expression of AHR in GH3 cells revealed a tumour suppressor potential independent of exogenous ligand activation by benzo α-pyrene (BαP). Cell cycle analysis and quantitative PCR of cell cycle regulator genes revealed that both unstimulated and BαP-stimulated AHR reduced E2F-driven transcription and altered expression of cell cycle regulator genes, thus increasing the percentage of cells in G0 /G1 phase and slowing the proliferation rate of GH3 cells. Co-immunoprecipitation confirmed the interaction between AHR and retinoblastoma (Rb1) protein supporting this as a functional mechanism for the observed reduction. Endogenous Ahr reduction using silencing RNA confirmed the tumour suppressive function of the Ahr. These data support a mechanistic pathway for the putative tumour suppressive role of AHR specifically in PA, possibly through its role as a cell cycle co-regulator, even in the absence of exogenous ligands.